Teacher-offered Forms of Support for Learners with Low Self-esteem and Suffering from Bullying - Meškauskienė, Asta; Barkauskaitė, Marijona (Pedagogika, 2015)
Purpose. The problem of bullying remains one of the major social problems in Lithuanian schools. But the acquired experience of practices in fighting the negative phenomenon enables professionals to improve the measures already taken and to foresee new methods in overcoming the problem. The purpose of the present article is to explore the teacher-offered forms of support for teenagers with low self-esteem and suffering from bullying. Methods and resources. The methods used in the study are research literature analysis and qualitative methods. The sample of the qualitative research comprises 86 teachers from schools of general secondary education, of different subjects, with different professional qualifications and experience, of different age groups. The teachers were asked to respond to half-structured questionnaires. Results. On the basis of the obtained data, it has been established that the most efficient forms of support for teenagers with low self-esteem and suffering from bullying were the ones involving the development of the sense of learner responsibility within school and class community (including the encouragement of empathy and tolerance, raising the awareness of human rights, creating the atmosphere of intolerance towards bullying, and initiating peer-support groups) as well as the enhancement of personal responsibility on the part of every individual who comes into contact with teenagers suffering from bullying (namely, peers, form tutor, social pedagogue, school psychologist, parents and others).